الاستراتيجية الجزائرية للأمن الطاقوي: رؤية الانتقال الطاقوي 2030 نموذجا The Algerian Energy Security Strategy: The Energy Transition Vision 2030 as a model - عطية, ادريس (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2024)
يشكل الأمن الطاقوي رهانا أساسيا من رهانات الأمن الوطني الشامل، وتسعى الجزائر على غرار كل دول العالم إلى تحقيق أمنها في هذا المجال بما يكفل استهلاكها المحلي ويضمن التصدير للخارج، بحيث تمتلك الجزائر مصادر طبيعية هائلة في مجال إنتاج الطاقات البديلة عن مصادر الطاقة الأحفورية، وتسعى هذه الدراسة إلى فحص البرنامج الوطني للانتقال الطاقوي الممثل في "رؤية 2030"، الذي تراعي فيه الجزائر مسألة البيئة واستدامتها والانفتاح على مجالات نظيفة تساهم في حماية المحيط وتطور الاقتصاد الأخضر وتحقيق العدالة المناخية. وتحاول هذه الدراسة ضبط الاستراتيجية الجزائرية لتحقيق الأمن الطاقوي المستدام، من خلال التحرك الجزائري والتخطيط الجيّد والرشيد والتسيير العقلاني وكذا حكامة السياسية العمومية للطاقة في إطار المشروع الوطني للانتقال الطاقوي. Abstract: Energy security constitutes a fundamental bet of the comprehensive national security bets, and Algeria, like all countries in the world, seeks to achieve its security in this area in a way that ensures its domestic consumption and guarantees exports abroad, so that Algeria has enormous natural resources in the field of producing energies alternative to fossil energy sources, and it seeks these The study examines the National Program for Energy Transition represented in "Vision 2030", in which Algeria takes into account the issue of the environment and its sustainability and openness to clean areas that contribute to protecting the ocean, developing the green economy and achieving climate justice. This study attempts to adjust the Algerian strategy to achieve sustainable energy security, through Algerian action, good planning and rationality, and rational management, as well as the general political governance of energy within the framework of the national project for energy transition.